درجة توظيف معلمي مادة التربية الوطنية والمدنية بالمرحلة الأساسية العليا لمشروعات التعلم الخدمي في التدريس والمعيقات التي تحول دون تنفيذها - طلافحة، حامد عبدالله علي (جامعة اليرموك - عمادة البحث العلمي, 2012)
هدفت الدراسة الكشف عن درجة توظيف معلمي مادة التربية الوطنية والمدنية بالمرحلة الأساسية العليا لمشروعات التعلم الخدمي في التدريس، ومعرفة أهم المعيقات التي تحول دون تنفيذها. وتكون أفراد الدراسة من جميع معلمي ومعلمات مادة التربية الوطنية والمدنية للمرحلة الأساسية العليا في مدارس مديرية تربية اربد الأول والثانية، وبلغ عددهم (131) معلماً ومعلمة، ولأغراض الدراسة تم إعداد أداة مكونة من جزأين: الأول لقياس درجة توظيف المعلمين لمشروعات التعلم الخدمي. والثاني لقياس المعيقات التي تحول دون تنفيذها، وقد تمتعت الأداة بدلالة صدق وثبات مقبولين. وأظهرت النتائج أن درجة توظيف المعلمين لمشروعات التعلم الخدمي جاءت بدرجة منخفضة، وأن درجة المعيقات التي تحول دون تنفيذ تلك المشروعات كبيرة، كما أظهرت النتائج وجود أثر لمتغيرات: الجنس والمؤهل العلمي وسنوات الخبرة في درجة توظيف المعلمين لمشروعات التعلم الخدمي. وأن هناك علاقة ارتباطيه متوسطة بين توظيف مشروعات التعلم الخدمي وبين معيقات تنفيذها. The study aimed to investigate the degree of employment of service learning projects in teaching, among teachers of citizenship education at upper basic stage, and the obstacles that prevent the employment of these projects.The study sample consisted of all citizenship education teachers for the upper basic stage, in the schools of first and second education directorates in Irbid governorate, with total (131) teachers. For the purposes of the study, the researcher prepared an instrument which consists of two parts: the first measures the degree of employment of service learning projects; and the second measures the obstacles that prevent employment in these projects. Content validity and reliability of the instrument was ensured. The results showed that the degree of employment of service learning projects among teachers is low, and the degree of obstacles that prevent the employment of these projects is high. The results also showed effect attributed to the variables: sex, academic qualification and experience, in the degree of employment of service learning projects. The results also showed there was a moderate correlation between the degree of employment of service learning projects and the obstacles that prevent the employment of these projects
625871 805399 722778 777363 816717 761434 755669 817230
Keywords: الأردن -- معلمو التربية الوطنية -- معلمو التربية المدنية -- مهنة التدريس -- طرق التدريس -- اربد -- التعليم المتوسط -- المهارات التدريسية -- توظيف المعلمين -- الكفايات التدريسية